Childhood Familial Victimization: An Exploration of Gender and Sexual Identity Using the Scale of Negative Family Interactions - Martinez, Katherine (Journal of interpersonal violence, 2021)
Familial violence poses a serious public health concern and has therefore received a considerable amount of attention from academics and practitioners alike. Research within this field has found that parent-to-parent and parent-to-child violence often occur simultaneously and are especially prevalent within households that suffer from social and environmental stressors. Sibling violence and its relationship to these other forms of familial violence has received considerably less attention, largely related to the widely held belief that sibling violence is natural, especially for boys. Using the Scale of Negative Family Interactions (SNFI), parent-to-child and sibling-to-sibling violence is investigated. Specifically, the relationship between participants’ gender and sexual identities and their reports of familial violence are explored to better understand participants’ gendered and sexed experiences. Data suggest that gender and sexual minorities may have a unique experience of familial violence, although further research is needed in this area.